Rural-urban linkage patterns through Agribusi-ness activities in reducing regional disparities: A case study of Mekarsari village and Unaaha City, Indonesia - Hasddin; Tonjaya Gede; Asrul; Jasman; Taufik; Azis Rudi; Mukaddas Jamal; Haydir; Husen Osu Oheputra; Ishak Al-Fian (Glasnik Srpskog Geografskog Društva)
Various efforts to overcome the gap between rural and urban, such as the implementation of the green revolution strategy to strengthen the agricultural sector in rural areas, have not produced optimal results. One solution to overcome this gap is to strengthen the relationship pattern between rural and urban. This study aims to explore the potential of agribusiness as a basis for the relationship between rural and urban, and to analyze the relationship pattern through agribusiness activities. This study took the case of Mekarsari Village and Unaaha City, Indonesia. A total of 121 farmers were involved in this study. Primary data were obtained through surveys and interviews, while secondary data were obtained through document reviews to then be analyzed descriptively qualitatively. This analysis reveals a mutually supportive relationship between rural and urban in the agribusiness sector. Rural act as the main producers of agricultural and livestock commodities, such as food crops, vegetables, fruits, and livestock, most of which are supplied to cities to meet consumption demand. Meanwhile, urban provide essential goods for rural areas to support production, such as fertilizers, seeds, pest control equipment, and household needs such as staple foods, clothing, and electronics. This flow of goods reflects an interdependent relation-ship that not only supports the agricultural and livestock sectors but also improves the quality of life of rural communities, ensures economic sustainability, and strengthens the social fabric of both regions.